TRAITEMENT VISUO-ATTENTIONNEL ET AUTOREGULATION DANS L'ENSEIGNEMENT/APPRENTISSAGE DE L'EXPRESSION ECRITE EN FLE CAS DES APPRENANTS DE 5EME ANNEE PRIMAIRE - MESSADI Rayen (My University, 2022)
Abstract Through our research work, we want to know how effective and advantageous Visio-attentional processing can be and does it allow the self-regulation of the scriptural competence of learners in French as a foreign language at the primary level. Our experiment aims to show the course of a writing activity, to determine the usefulness of this treatment in the teaching / learning of written expression in French as a foreign language in order to begin an analytical study of the productions of the experimental group. of this study, that the Visio-attentional processing in writing activities and particularly in French as a foreign language class, is an opportunity for learners to systematically practice written expression ------------------ Résumé À travers notre travail de recherche, nous voulons savoir à quel point le traitement Visio- attentionnel peut-il être efficace et avantageux et permet-il l’autorégulation de la compétence scripturale des apprenants en FLE au primaire. Notre expérimentation vise à montrer le déroulement d’une activité d’écriture, pour déterminer l’utilité de ce traitement dans l’enseignement/apprentissage de l’expression écrite en FLE afin d’entamer une étude analytique des productions du groupe expérimental Il ressort de cette étude, que le traitement Visio- attentionnel dans les activités d’écriture et particulièrement en classe de FLE, c’est une occasion aux apprenants pour pratiquer systématiquement l’expression écrite.